Pengaruh Metode Peer Tutoring dan Adversity Quotient terhadap Hasil Belajar Siswa Mata Pelajaran Siklus Akuntansi Perusahaan Dagang SMKN 1 Painan - Muliani, Nur Aisya; Sofia, Nita (Jurnal Ecogen, 2024)
This research aims to determine the effect of peer tutoring and adversity quotient methods on student learning outcomes in the elective subject accounting cycle for trading companies in class XI Accounting at SMK N 1 Painan. The research method used was quasi-experimental with the Two-Way ANOVA testing technique. The total sample was 52 class XI accounting students at SMKN 1 Painan, divided into 2 groups, including 26 students in the experimental group and 26 students in the control group. The results of this research are: 1) There are differences in learning outcomes in the trading company accounting cycle elective subjects taught using the peer tutoring learning method which are higher than those of students taught using the lecture learning method in class XI Accounting at SMKN 1 Painan. 2) The learning outcomes of class XI Accounting students at SMKN 1 Painan who have a higher adversity quotient are significantly higher than students who have a low adversity quotient. 3) There is an interaction between the peer tutoring learning method and the adversity quotient on learning outcomes in the elective subject of the trading company accounting cycle in class XI Accounting at SMKN 1 Painan